Reaction selectivity-regulation via interfacial reconstruction for preventing hazardous slime generation: driving mechanism of Pb-based anode with oxygen vacancy-rich MnO2 - Zhuang, Siwei (2024)
Limited selectivity in coexisted anodic reactions on lead-based anodes leads to severe lead-dissolution, anodic slime-generation and high energy-consumption. Herein, anodic reaction selectivity was regulated by phase-controlled MnO2 (MnO2-PC) on lead-based anodes which was prepared under a lower voltage and a higher Mn2+ concentration. Compared with α-MnO2 formed under normal conditions, composite phase of γ-MnO2 and ε-MnO2 was obtained from MnO2-PC with specific crystal planes exposure and rich oxygen vacancy defects enabling higher oxygen evolution reaction selectivity (OER, overpotential reduced by ∼99 mV). Meanwhile, reaction of lead corrosion and manganese oxidation, as the main reasons for generation of hazardous lead-containing slime, were synergistically suppressed by 86.8% and 91.7%, respectively. Density functional theory (DFT) calculations further clarified that the change in coordinative environment of Mn and O brought lower energy barrier of rate-determining step of OER and stronger electron delocalization ability of MnO2, beneficial for promoting the catalysis of OER. MnO2-PC also displayed excellent inhibition effects on the generation and accumulation of Mn3+, an important precursor of MnO2 slime, and changed the selectivity in the oxidative path of Mn2+. The long-term electrolysis tests proved the stable performance of Pb–Ag/MnO2-PC. This study provides an efficient, low-cost, high economic benefits and environmental-friendly strategy for designing target functional materials towards reaction selectivity regulation via phase-control and microstructure reconstruction.